The terrestial fauna of Apid Island, Inopacan, Leyte, Philippines - Allgaier, Christoph; Schaefer, Frank; Ceniza, Maria Juliet C.; Martin, Konrad (Annals of Tropical Research, 1999)
The terrestrial fauna of Apid Island in different types of habitat (mainly agricultural) was studied by sweep-netting of arthropods; hand sampling of species living on the ground and by visual observations. Results showed that the island is relatively species-poor compared to an area of the same size and habitat type on mainland Leyte. This is mainly due to (1) the small size of the island, (2) the lack of running waters, and (3) human activities which have removed most parts of the natural vegetation. As a common tendency, the most abundant faunal groups are those which show a preference for more open and dryer habitats than a tropical rainforest. The most abundant herbivores are grasshoppers, and the most abundant predators are spiders (in all habitat types). Land snails are the common group of species living in the soil, which is explained by the fact that Apid Island is built up of limestone.